1967
DOI: 10.1107/s0365110x67000362
|View full text |Cite
|
Sign up to set email alerts
|

The crystal and molecular structure of hydroxyquinones and salts of hydroxyquinones. V. Hydronium nitranilate, nitranilic acid hexahydrate

Abstract: The structure of nitranilic acid hexahydrate has been determined by use of partial three-dimensional data. The cell dimensions are: a= 3-657, b= 19.399, c= 9"184/~, B=94.28 °. The space group is P21/c and Z= 2. The geometry of the carbon ring system is similar to that found in chloranilate and nitranilate ions, and the carbon-oxygen bonds are of equal length (1-22 A, the same as in nitranilate). There is thus strong evidence that the substance is hydrated hydronium nitranilate. The ring is planar, but the nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…When using the [M III (acac 2 (38), have been prepared and characterized by Coronado et al [172]. The 2D anilate-based networks show the common honeycomb anionic packing pattern but a novel type of structure where the cations are placed into the hexagonal channels of the 2D network has been afforded due to the smaller size of the [Fe III (acac 2 -trien)] + or [Ga III (acac 2 -trien)] + complex with respect to the templating cations used in previous compounds of this type, where they are placed in between the anionic layers.…”
Section: Spin-crossover Complexesmentioning
confidence: 99%
“…When using the [M III (acac 2 (38), have been prepared and characterized by Coronado et al [172]. The 2D anilate-based networks show the common honeycomb anionic packing pattern but a novel type of structure where the cations are placed into the hexagonal channels of the 2D network has been afforded due to the smaller size of the [Fe III (acac 2 -trien)] + or [Ga III (acac 2 -trien)] + complex with respect to the templating cations used in previous compounds of this type, where they are placed in between the anionic layers.…”
Section: Spin-crossover Complexesmentioning
confidence: 99%
“…In the previous X-ray study of hydronium nitranilate (Andersen, 1967a) the hydrogen-atom positions were not determined. Since all the hydrogen atoms in the water molecules have more than two oxygen …”
Section: The Crystal Structurementioning
confidence: 98%
“…4 of Andersen, 1967a). The columns are surrounded on all sides by water molecules and hydronium ions.…”
Section: The Crystal Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Andersen (1967c) suggested that the equalization of C(2)-C(3) and C(3)-C(1') in (VIII) is brought about by disorder in the crystal. The same explanation is given for the two equal C-O bonds.…”
Section: Details Of the Structures Of Hydroxybenzoquinonesmentioning
confidence: 99%